ISSUES OF SMALL BUSINESS DEVELOPMENT BASED ON PUBLIC-PRIVATE PARTNERSHIP - Gayratjon Akbarov (Bright Mind Publishing, 2025)
This article discusses about the characteristics of small business and public-private partnership, directions of cooperation between the state and business entities, the advantages of small business organization based on public-private partnership, and given scientific recommendations and proposals.
Keywords: Small business, business entities, functions and tasks of the state, state partner, private partner, public-private partnership.